Functional Change and the Peri‐Urban Region: Food Systems and Agricultural Vulnerability. Issue 3 (20th September 2013) - Butt, Andrew
<x xml:space="preserve">Abstract</x> The formation of extensive peri‐urban regions around Australia's cities as sites of population growth and land use change has resulted in a critical divergence in agricultural production patterns over several decades. Unlike more distant agricultural regions where farm numbers have typically declined, peri‐urban areas have experienced a proliferation of small and sub‐commercial farm businesses and the continued presence of fewer large operations. Despite this, agricultural production has not collapsed in these regions. This article reviews changes in farm output and structure occurring in some example peri‐urban regions with a view to exploring the nature of viability and vulnerability of the agricultural systems in these areas. It concludes that farming in these regions is changing in significantly different ways to other agricultural regions. The key components of peri‐urban farming productivity centre on a few high value activities, and some, such as intensive poultry, face significant constraints to growth through population and landscape pressures in an effectively post‐productive environment. This presents consequent risks to ongoing food production in the regions closest to our largest cities. The majority of peri‐urban farming has the potential to provide important landscape services functions, but is unable to adjust to changing productivity regimes creating vulnerabilities for peri‐urban farming systems.